2015
DOI: 10.1080/15228932.2015.997611
|View full text |Cite
|
Sign up to set email alerts
|

Observations From Canadian Practitioners About the Investigation and Prosecution of Crimes Involving Child and Adult Witnesses

Abstract: Hundreds of scientific studies on the competencies and limitations of eyewitnesses have been published, but few have sought input from front-line forensic interviewers. In the current study, a research agenda was established with in-depth input from 13 forensic interviewers. Interviewers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…There are several legal reasons for the need to particularize separate incidents such as being able to lay specific charges and determine sentencing. Our previous research (e.g., Roberts & Powell, 2006), case law (e.g., R v. B [G], 1990), surveys of interviewers (e.g., Roberts & Cameron, 2015), and our discussions with investigators indicate that child witnesses find it difficult to connect 'particulars' or details with the exact individual acts or occurrences. Typically, children are confused between occurrences, even though much of what they recall is accurate (Powell & Thomson, 1996).…”
Section: Children's Memory and The Forensic Interviewmentioning
confidence: 99%
“…There are several legal reasons for the need to particularize separate incidents such as being able to lay specific charges and determine sentencing. Our previous research (e.g., Roberts & Powell, 2006), case law (e.g., R v. B [G], 1990), surveys of interviewers (e.g., Roberts & Cameron, 2015), and our discussions with investigators indicate that child witnesses find it difficult to connect 'particulars' or details with the exact individual acts or occurrences. Typically, children are confused between occurrences, even though much of what they recall is accurate (Powell & Thomson, 1996).…”
Section: Children's Memory and The Forensic Interviewmentioning
confidence: 99%
“…The most common response (discussed by 27% of the practitioners) was to interview young children, citing for example the need to phrase developmentally sensitive questions and keeping the children's attention. Roberts and Cameron (2015) also surveyed 8 forensic child interviewers from Canada about their views on the usefulness of specific interviewing techniques with children of different ages. In line with Rowback Rivard and Schrieber Compo (2017), the Canadian practitioners reported difficulties eliciting adequate accounts from children below the age of six during forensic interviews.…”
mentioning
confidence: 99%
“…Furthermore, some expressed concerns regarding the testimony of adolescents. Roberts and Cameron (2015) emphasized the need for further research on witness interviews with adolescents, as the majority of studies on this age group has focused on suspect interrogations (see for example Redlich, 2010).…”
mentioning
confidence: 99%
“…Interviewers consistently discussed ground rules, asked for a promise to tell the truth, and conducted rapport and free-narrative practice. Evaluations from other countries have shown that interviewers often omit ground rules (Luther et al, 2014;Roberts & Cameron 2015;Sternberg et al, 2001) or episodic recall practice (La Luther et al, 2014;Westcott & Kynan, 2006).…”
Section: Evaluation Of Forensic Interviewing Practice In New Zealandmentioning
confidence: 99%